A brief overview of sustained released drug delivery system - Priyanka Prajapat; Dilip Agrawal; Gaurav Bhaduka (Journal of Applied Pharmaceutical Research, 2022)
The most popular and patient-friendly method of drug administration is often thought to be the oral route of administration. Compared to conventional release formulations, advancements in formulation technology, including modified release dosage forms or sustained release oral dosage forms, have been extensively accepted. A sustained release dosage form provides a prolonged release of the drug over an extended period, thereby giving better patient compliance and enhanced bioavailability. Sustain release systems are considered a wiser approach for drugs with short half-lives requiring repeated dosing. Sustained release drug delivery has a range of advantages over conventional dosage forms, including increased patient compliance due to less frequent drug administration, significantly reduced steady state drug level fluctuations, maximum drug utilization, the increased safety margin of potent drugs, lower healthcare costs due to improved therapy, and shorter treatment times. The present review focuses on design, fabrication, and various factors that influence the performance of sustained-release dosage forms.